P2X7 Receptor Expression and Signaling on Dendritic Cells and CD4+ T Cells is Not Required but Can Enhance Th17 Differentiation - Yang, Yin; Story, Meaghan E.; Hao, Xingxing; Sumpter, Tina L.; Mathers, Alicia R. (Frontiers in Cell and Developmental Biology, 2022)
The purinergic receptor P2X7 (P2X7R) is important in inflammasome activation and generally considered to favor proinflammatory immune responses. However, there is still a limited understanding of the role of P2X7R signaling in Th cell differentiation, particularly, Th17 differentiation. Herein, the impact of P2X7R signaling on primary Th17 and Th1 cell responses was examined when P2X7R was expressed specifically on dendritic cells (DCs) and CD4+ T cells. Surprisingly, global genetic ablation and pharmacological inhibition of the P2X7R did not affect the generation of Th17 and Th1 development in response to immunization with Complete Freund’s Adjuvant and the model antigens, KLH or OVA. However, in-depth in vitro and in vivo investigations revealed differences in the balance of Th1/Th17 differentiation when P2X7R blockade was restricted to either DCs or CD4+ T cells. In this regard, in vitro DCs treated with a P2X7R agonist released more IL-6 and IL-1β and induced a more robust Th17 response in mixed leukocyte reactions when compared to controls. To test the hypothesis that P2X7R signaling specifically in DCs enhances Th17 responses in vivo, DC-specific P2X7R deficient chimeras were immunized with CFA and OVA. In this model, the P2X7R expression on DCs decreased the Th1 response without impacting Th17 responses. Following an assessment of CD4+ T cell P2X7R signaling, it was determined that in vitro P2X7R sufficient T cells develop an increased Th17 and suppressed Th1 differentiation profile. In vivo, P2X7R expression on CD4+ T cells had no effect on Th17 differentiation but likewise significantly suppressed the Th1 response, thereby skewing the immune balance. Interestingly, it appears that WT OT-II Th1 cells are more sensitive to P2X7R-induced cell death as evidence by a decrease in cell number and an increase in T cell death. Overall, these studies indicate that in vitro P2X7R signaling does enhances Th17 responses, which suggests that compensatory Th17 differentiation mechanisms are utilized in vivo in the absence of P2X7R signaling.